Investigation of Geriatric Patients with Abdominal Pain Admitted to Emergency Department. (30th May 2018) - Henden Çam, Pınar; Baydin, Ahmet; Yürüker, Savaş; Erenler, Ali Kemal; Şengüldür, Erdinç
Abstract : Introduction . The aim of this study is to detect the possible reasons of abdominal pain in the patients aged 65 and older admitted to emergency department (ED) with complaint of abdominal pain which is not related to trauma, to determine the length of hospitalization of old (65–75 age) and elderly (aged 75 and older) patients, and to define the hospitalization and mortality rates. Material and Methods . In the study, 336 patients were included. Groups were compared in respect to gender, internal or surgical prediagnoses, complaints accompanying abdominal pain, vital findings, comorbidities, requested consultations, hospitalizing service, waiting time in the ED and in the hospital, and treatment methods. Results . Of the patients, 48.2% were male, and 51.8% were female. While 52.4% of the patients were in 65–74 age group, 47.6% of them were aged 75 years and above. An internal disease was detected in 76.8% of the patients as an origin of abdominal pain. Most common prediagnoses were biliary diseases and diseases related to biliary tract followed by nonspecific abdominal pain, abdominal pain secondary to malignity, ileus, and acute gastroenteritis, respectively. The most frequent finding accompanying abdominal pain was vomiting. The most frequent chronic disease accompanying abdominal pain was hypertension in both age groups. We observed that 75.9% of the patients required consultation. We detected that 48.8% of the patients with abdominal pain were hospitalized and they were hospitalized mostly by gastroenterology ward (24.8%). Surgical treatments were applied to the 17.6% of the patients with abdominal pain. Conclusion . Clinical findings become indistinct by age, and differential diagnosis of abdominal pain gets more difficult in geriatric patients. Therefore, physicians should consider age related physiological changes in order to distinguish geriatric patients admitted to emergency service with abdominal pain from pathological cases requiring immediate surgical operation.